El estado de embriaguez y el consumo de sustancias psicoactivas como causa justificada de finalización del contrato de trabajo (2023)
This investigation carries out an analysis between the existing conflicts in labor relations when it is necessary to apply just causes in the termination of an employment contract when these are motivated by the consumption of alcohol and psychoactive substances.Therefore, an emphasis is made on Colombian labor regulations and the alternatives that this gives for the justification of dismissals, therefore, the conclusions are issued taking into account the norm and the need for particularity in the case study.